Pembinaan Dan Penerapan Mesin Pencacah Limbah Pertanian Bagi Kelompok Petani Di Kab. Rejang Lebong - Harry Prayoga Setyawan; Fauzi Widyawati; Apri Setiawan; Hanni Maksum (CV. Multi Kreasi Media, 2026)
The agricultural sector in Babakan Baru Village faces significant challenges in managing crop residues, which are traditionally burned, leading to environmental pollution. This Community Service (PkM) program implements Appropriate Technology (TTG) through an agricultural waste shredding machine to enhance farmers' productivity and self-sufficiency. The methodology involves partner coordination, CAD-based design, manufacturing, technical assistance, and operational training. The project successfully developed a shredder unit with a 100 kg/hour capacity powered by a 7.5 HP gasoline engine. This implementation delivers transformative impacts: technically, it increases the efficiency of converting waste into compost raw materials, while economically, it reduces dependence on commercial chemical fertilizers. Furthermore, the training improved the farmer groups' human resource capacity regarding machine maintenance and Occupational Health and Safety (OHS) procedures. Overall, the program fosters sustainable agricultural modernization that is environmentally friendly and economically beneficial in Rejang Lebong Regency.